PENGARUH EMPLOYEE ENGAGEMENT DAN KESEJAHTERAAN KARYAWAN TERHADAP EMPLOYEE RETENTION MELALUI STRATEGI TALENT MANAJEMEN BISNIS - Dedi Rianto Rahadi; Az-zahra Riyadhul Jannah, Kevin Haryo Alonso (CV. ADIBA AISHA AMIRA, 2024)
This research aims to investigate the influence of employee engagement and happiness on employee retention through the implementation of talent management strategies in the context of Business Management. The research method uses Structural Equation Modeling - Partial Least Squares (SEM-PLS) using Smart-PLS software. The research population includes employees at PT ABC Cikaarang. Data collection was carried out using a questionnaire. The research results show high reliability in the variable measurement tools used, especially employee uncertainty, employee retention, employee welfare, and talent management. Hypothesis analysis shows that there is a significant influence between employee retention, employee retention and talent management. However, it was found that the relationship between employee well-being and talent management was not significant. The implication is that increasing employee engagement and happiness can strengthen the relationship with employee retention and talent management, which will have a positive impact on human resource management in business organizations. These findings provide theoretical contributions regarding the dynamics of key human resource management variables, while providing practical guidance for organizational leaders